Financial Performance Indicators and Stock Returns: A Decade-Long Analysis of MBI10 Firms in North Macedonia - Malchev, Bojan (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2023)
This paper investigates the relationship between financial performance indicators and annual stock returns of the MBI10 companies in North Macedonia over a ten-year period from 2013 to 2022. A total of 100 observations from the Macedonian stock market index (MBI10) are analyzed, using audited financial statements as the primary data source. The financial performance indicators studied include Return on Assets (ROA), Return on Equity (ROE), Earnings per Share (EPS), and Dividend per Share (DPS). A multiple linear regression model is applied to examine the impact of these indicators on annual stock returns, with the model estimated through ordinary least squares (OLS) estimation. The research tests four hypotheses, aiming to establish significant positive relationships between ROA and Stock Return, as well as EPS and Stock Return. The results confirm the hypotheses related to ROA and EPS, with significant positive impacts on Stock Return. However, the relationships between ROE, DPS, and Stock Return lack statistical significance. The findings suggest that the financial performance indicators considered in this study only account for a limited proportion (4.9%) of the variations in Stock Return, indicating the influence of other essential factors not included in the model. To enhance the reliability of the findings, a robustness check was conducted by introducing two control variables: Macedonian GDP annual real growth rates, and DAX30 Index annual rate of return. The regression model, including these control variables, exhibited almost the same results as the model without them. Furthermore, the model with the control variables demonstrated a slightly higher Adjusted R Square value (0.058) compared to the model without them (0.049), implying a slightly improved explanatory power.This study highlights the complexities of the Macedonian stock market and emphasizes the importance of investigating additional factors that significantly contribute to stock price movements and returns in this specific market context.
Keywords: Stock return; ROA; ROE; EPS; DPS